Manajemen Kearsipan dalam Penyelenggaraan Administrasi Negara di Kantor Kejaksaan Negeri Padang - Rizki Aprison; Syamsir Syamsir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This research was conducted at the Padang Public Prosecutor's Office to describe archival management in the administration of state administration in the Padang District Attorney's office. The data collection technique was carried out by purposive sampling and snowball techniques, which means that data collection was carried out based on direct field results taken from interviews until the data obtained was saturated at the Padang District Attorney's office. The data analysis technique used in this research is descriptive analysis, which is to provide a comprehensive overview of the research. With the various methods used, it is hoped that this research can provide a clear and precise description of the data and problems that exist later. Archival management at the prosecutor's office has been carried out quite well, but the facilities and infrastructure are still simple and there are no archivist employees. However, the Padang District Attorney's office is trying to fix the problems of archival management with the attention of the leadership to the employees who manage the archives, adding facilities and infrastructure for archiving and as soon as possible to destroy archives that are no longer in use.